2020
DOI: 10.3390/cells9092015
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for the Use of Radiation-Activated Mesenchymal Stromal/Stem Cells in Acute Respiratory Distress Syndrome

Abstract: We have previously shown that the combination of radiotherapy with human umbilical-cord-derived mesenchymal stromal/stem cells (MSCs) cell therapy significantly reduces the size of the xenotumors in mice, both in the directly irradiated tumor and in the distant nonirradiated tumor or its metastasis. We have also shown that exosomes secreted from MSCs preirradiated with 2 Gy are quantitatively, functionally and qualitatively different from the exosomes secreted from nonirradiated mesenchymal cells, and also tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…As with X-rays, exposure of MSC to UV light [44] or heat [45] induces increased release of anti-tumor or immunogenic factors, such as TNF-α and IFN-γ. In addition, enhanced production of annexin A1 in radiotherapy-stimulated MSC can relay anti-tumor signals [46,47]. This may provide superior therapeutic effectiveness by a combined stimulation of MSC with radiotherapy and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…As with X-rays, exposure of MSC to UV light [44] or heat [45] induces increased release of anti-tumor or immunogenic factors, such as TNF-α and IFN-γ. In addition, enhanced production of annexin A1 in radiotherapy-stimulated MSC can relay anti-tumor signals [46,47]. This may provide superior therapeutic effectiveness by a combined stimulation of MSC with radiotherapy and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these drugs exert therapeutic efficacies that are associated with regulation of the immune system. In addition, since MSCs have an immunosuppressive effect, and associated clinical trial data have shown significant therapeutic efficacy in severe cases of COVID-19 (78)(79)(80), MSC-based therapy could be a promising strategy for the reduction of inflammatory cytokine release in these patients. Therefore, we hypothesize that immunoregulatory therapy is currently the most promising treatment for severe COVID-19, especially for the elderly patients or those with underlying diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The authors report on key components of cell–cell or cell–matrix adhesion, including annexins and integrins, and link it with enhanced tumor cell death. It was also noted that the amount of protein present in pre-irradiated cells was 1.5 times greater compared to nonirradiated controls and this finding correlated with enhanced anti-tumor activity when combined with radiation therapy [ 84 ].…”
Section: Enhancement Of Effect Through Differentiation Prior To Engra...mentioning
confidence: 99%